Novel TALEN-generated mCitrine-FANCD2 fusion reporter mouse model for in vivo research of DNA damage response - Sabol, Maja; Akbudak, M Aydın; Fricova, Dominika; Beck, Inken; Sedlacek, Radislav (DNA repair, 2020)
Reporter gene mouse lines are routinely used for studies related to functional genomics, proteomics, cell biology or cell-based drug screenings, and represent a crucial platform for in vivo research. In the generation of knock-in reporter lines, new gene targeting methods provide several advantages over the standard transgenic techniques. First of all, specific targeting of the genome allows expression of the reporter gene under controlled conditions, whether in a specific locus in the genome or in a "safe harbor" locus. Historically, the ROSA26 locus is used for gene knock-in strategies by homologous recombination in mouse embryonic stem cells. The other preferred place for integration of the reporter transgene in the mouse genome is the endogenous promoter of a target gene. In this study, we employed TALENs to generate a reporter fusion protein expressed from its native promoter. For monitoring DNA damage response, we generated a mouse line expressing a mCitrine-tagged version of the FANCD2 protein, involved in DNA damage response and repair, and the Fanconi anemia (FA) pathway. This model could be a valuable tool for in vivo investigation of DNA damage.
Keywords: Models, Animal; reportérové geny; modely u zvířat; bakteriální proteiny; zvířata; Genes, Reporter; Recombinant Fusion Proteins; Animals; luminescentní proteiny; TALENs; Mice; oprava DNA; Luminescent Proteins; poškození DNA; myši; myši inbrední C57BL; protein FANCD2; rekombinantní fúzní proteiny; Transcription Activator-Like Effector Nucleases; DNA Damage; DNA Repair; Bacterial Proteins; Fanconi Anemia Complementation Group D2 Protein; Mice, Inbred C57BL